2022
DOI: 10.1177/25148486221133282
|View full text |Cite
|
Sign up to set email alerts
|

Race, citizenship, and belonging in the pursuit of water and climate justice in California

Abstract: Systemic inequalities, which affect how water is distributed and used, underlie water insecurities in higher-income (global North) countries. We explore the interlinkages between municipal decision-making and infrastructure to understand how urban climate justice can be advanced through engaging with state-like forms of governance. Drawing on archival information, spatial analysis, participant observation, and semi-structured interviews in the underbounded Latinx community of East Porterville, California, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…While drawing a causal relationship between race and water insecurity is not within the scope of this research, the 2020 UN World Water Report does explicitly relate water insecurity and intersectionality, especially regarding race and class ( UN Water, 2020). Peer-reviewed studies on this issue, however, overwhelmingly exist in the North American context (e.g., Deitz and Meehan, 2019;Dickin and Gabrielsson, 2023;Harrington et al, 2023;Meńdez-Barrientos et al, 2023;Workman and Shah, 2023). For example, a spatial analysis of water insecurity across the United States by Deitz and Meehan (2019) found that deficiencies in household water infrastructure are concentrated in regions typically inhabited by racialized groups.…”
Section: The Role Of Colonialism and Race In Marine Ecotourism And Wa...mentioning
confidence: 99%
“…While drawing a causal relationship between race and water insecurity is not within the scope of this research, the 2020 UN World Water Report does explicitly relate water insecurity and intersectionality, especially regarding race and class ( UN Water, 2020). Peer-reviewed studies on this issue, however, overwhelmingly exist in the North American context (e.g., Deitz and Meehan, 2019;Dickin and Gabrielsson, 2023;Harrington et al, 2023;Meńdez-Barrientos et al, 2023;Workman and Shah, 2023). For example, a spatial analysis of water insecurity across the United States by Deitz and Meehan (2019) found that deficiencies in household water infrastructure are concentrated in regions typically inhabited by racialized groups.…”
Section: The Role Of Colonialism and Race In Marine Ecotourism And Wa...mentioning
confidence: 99%
“…9–10). When actors lack the resources or capacity to participate in deliberation or are unfairly prevented from doing so, potentially due to historical and on‐going marginalization (Méndez‐Barrientos et al, 2022; O'Riordan et al, 2019; Wilson et al, 2022), procedural equity is undermined (Brisbois & de Loë, 2016; Choi & Robertson, 2014; Leach, 2006; Lubell et al, 2017; Morrison et al, 2019; Newig et al, 2018). This can increase the “democratic deficit” between more and less powerful participants (Nabatchi, 2010).…”
Section: Designing Equitable Collaborative Water Governancementioning
confidence: 99%
“…Colonial, racial, gendered, ableist, class, and caste systems of power and their place-based outcomes (re)produce household water insecurities, and associated adverse social, economic, physical, and mental wellbeing outcomes (Crow and Sultana, 2002;Daigle, 2018;Deitz and Meehan, 2019;Dewachter et al, 2018;Duignan et al, 2022;Gerlak et al, 2022;Jepson et al, 2017;Jones et al, 2005;Leder et al, 2017;Loftus, 2014;Lu et al, 2014;Mawani, 2022;Meehan et al, 2020;Méndez-Barrientos et al, 2022;O'Leary, 2019;Radonic and Jacob, 2021;Ranganathan, 2016;Shah et al, 2021;Sultana, 2009Sultana, , 2020Truelove, 2019;Wilson et al, 2021;Wolbring, 2011;Wutich et al, 2022). This section reviews water affordability and insecurity experiences at the intersections of gender and class oppression.…”
Section: Intersectionality Water Affordability and Insecuritymentioning
confidence: 99%